(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: Reporting the incidence of contralateral patent processus vaginali (CPPV) in pediatric patients with unilateral inguinal hernia. Methods: The study was conducted from November 2010 - February 2012. Patient’s identity were recorded for registration number, name, age, gender, address and date of examination. The surgery was conducted by a trainee pediatric surgeon as a researcher and resident. High ligation procedure and diagnostic of contralateral PPV. Results: This study included 40 pediatric patients of various ages diagnosed with lateral inguinal hernia. There were 31 male patients (77.5%), 24 patients (60%) with right inguinal hernia patients, and 14 patients (35%) aged 0-1 years. Conclusion: The transinguinal laparoscopic contralateral PPV technique is helpful in diagnosing the presence of contralateral PPV. The incidence of contralateral PPV in this study was 27.5%. Furthermore, early age increased the incidence of contralateral PPV.